Cell-type-specific activity of the human papillomavirus type 18 upstream regulatory region in transgenic mice and its modulation by tetradecanoyl phorbol acetate and glucocorticoids. - Cid, A (1993)
The upstream regulatory region (URR) of human papillomavirus type 18 (HPV-18) harbors transcriptional promoter and enhancer elements which are thought to determine the cell-type specificity of the virus. In order to study the regulation of HPV-18 expression in vivo, we constructed transgenic mice carrying the bacterial lacZ gene under the control of the HPV-18 URR. Analysis of beta-galactosidase activity by histochemical staining of tissue sections of four independent transgenic mice showed that the viral promoter was specifically active in epithelial cells within a variety of organs (e.g., tongue, ovary, uterus, testis, and small intestine). Very strong staining was observed in newborn transgenic mice in contrast to a weak activity found during fetal life. Determination of beta-galactosidase activity in crude extracts from tissues of three lines of transgenic mice proved to be a useful tool for a quantitative analysis of transgene expression. In mice from two different transgenic lines treated with dexamethasone such measurements revealed a biphasic effect of the hormone on the activity of the enzyme in the stratified epithelium of the tongue (transient increase followed by a decrease). Northern (RNA) blot analysis showed similar changes in beta-galactosidase mRNA in that tissue. Treatment with tetradecanoyl phorbol acetate (TPA) led to a twofold increase in both enzymatic activity and mRNA levels. Finally, combined treatments with dexamethasone and TPA showed that both factors interfered with each other in their respective effects on transgene expression, suggesting that a cross-talk mechanism between transcription factors could be involved in the regulation of the HPV-18 URR.